Ensuring Quality and Excellence: The Role of Accreditation in Agricultural Graduate Education - Ludivico B. Homillano (New Advances in Business, Management and Economics Vol. 4, 2025)
To examine the development and present state of agricultural graduate programs at Central Bicol State University of Agriculture (CBSUA) from 2017 to 2023, the study used a mixed-methods research technique. In the context of a state agricultural university in the Philippines, the study employed an analytical approach combining qualitative assessments of institutional capabilities and quantitative data evaluation of enrollment patterns, faculty profiles, and accreditation standards. The Master of Science in Agricultural Education program expansion was proven through a longitudinal study using a 4.2% compound annual growth rate and an 89.4% retention coefficient. The percentage of female academics in the faculty ranged from 57% to 89% across all programs, while the PhD Plant Science specialization contained the highest concentration of doctorate-qualified teachers. The COVID-19 pandemic required institutional performance measures to adapt successfully because student retention rates remained at 94.8%. The evaluation of academic excellence led to Level IV accreditation for the Agricultural Education and Agricultural Extension programs in 2021. The systematic analysis revealed three main operational limitations, which included inadequate resource distribution systems, unbalanced faculty work responsibilities, and limited industrial collaboration frameworks. The study recommends two strategic measures involving the formation of a Graduate School Resource Management Office and the establishment of a Graduate School-Industry Advisory Board. The study helps confirm how agricultural graduate education develops through research into capacity-building relationships between institutional frameworks and stakeholder participation measures for academic quality advancement.